Fostering Success: Investigating Knowledge Sharing, Leadership, Work Behavior and Performance - I Made Hadi Purnantara; M Huanza; Didi Pianda; Marwan Effendi; Waqiah Waqiah (Jurnal Informatika Ekonomi Bisnis, 2023)
This study examines the relationships between knowledge sharing, effective leadership, work behavior, and performance in Sekretariat Daerah Denpasar. The aim is to investigate how knowledge sharing and effective leadership influence performance, mediated by work behavior. Data was collected from 83 respondents through questionnaires, and multiple linear regression and path analysis were used for analysis. The results demonstrate significant and positive effects of knowledge sharing and effective leadership on work behavior within Sekretariat Daerah Denpasar. This emphasizes the importance of promoting a culture of knowledge sharing and developing effective leadership behaviors to enhance employee work behaviors. Furthermore, the study reveals significant and positive impacts of knowledge sharing, effective leadership, and work behavior on performance, highlighting their role in driving organizational success. Importantly, work behavior is identified as a mediating variable in the relationships between knowledge sharing, effective leadership, and performance. Positive work behaviors, including collaboration, communication, and adaptability, mediate the influence of knowledge sharing and effective leadership on performance outcomes. These findings underscore the significance of fostering positive work behaviors and creating a supportive work environment. The practical implications suggest that Sekretariat Daerah Denpasar should prioritize initiatives that enhance knowledge sharing practices, develop effective leadership skills, and foster positive work behaviors. By investing in these areas, the organization can improve employee engagement, collaboration, and productivity, ultimately leading to enhanced performance outcomes.